The Medium-Term Budget Forecast as a Tool for the Formulation of Bulgaria‘s Fiscal Policy - Kostov, Lyuboslav (Research Papers, 2024)
The purpose of the report is to assess the degree of credibility in the main budget parameters in the medium-term budget forecast of the Ministry of Finance of Republic of Bulgaria. An overview of the main fiscal parameters in the period 2016 – 2021 was made, as well as their implementation. It is clear that in the observed period there is a significant discrepancy between the originally planned parameters in the revenue and expenditure part of the State Budget of the Republic of Bulgaria, from the actual reported ones after that.
Keywords: Fiscal policy; Revenues; Expenditures; Budget balance